Identity Crisis Of The Clown In Dazai Osamu’s No Longer Human Using Erik Erikson Psychosocial Theory - Yuli Astuti, Amelia; Hanif, Abdul (Jurnal Ilmiah Pendidikan Scholastic, 2025)
This research is titled "The Identity Crisis of the Clown in Dazai Osamu's No Longer Human Using Erik Erikson's Psychosocial Theory." This study aims to identify the causes of the identity crisis and alienation experienced by Oba Yozo in the novel No Longer Human, using the psychosocial development stage theory developed by Erik Erikson, with a focus on the fifth stage, "Identity vs. Role Confusion." The method used in this research is qualitative, with the novel No Longer Human as the data source. The research was conducted using data collection techniques such as reading and noting important parts of the novel, and by recording and quoting text from the novel. The research results show that Oba Yozo experienced alienation and confusion from a young age in determining his role in life, both for himself and for society. This led Oba Yozo to create a "mask" to defend himself from the outside world. The alienation, confusion, and the "mask" he created exacerbated Yozo's identity crisis, making him feel like he had failed to be human. This research shows that Yōzō's identity crisis was not only caused by internal factors, but was also influenced by a lack of family and social support. This highlights the importance of affection, support, and healthy social interaction in helping individuals build a complete sense of self and preventing them from feeling alienated from themselves and society.